CRF1 and CRF2 receptors in the lateral hypothalamus differently modulate the baroreflex function in unanesthetized rats - Reis-Silva, Lilian L. [UNESP] (2021)
The lateral hypothalamus (LH) is a diencephalic structure that has been considered part of the central circuitry regulating the baroreflex function. However, the local neurochemical mechanisms involved in baroreflex control by this hypothalamic area are poorly understood. Therefore, in the present study we investigated the role of corticotropin-releasing factor (CRF) neurotransmission within the LH acting via local CRF1 and CRF2 receptors in cardiac baroreflex responses in unanesthetized rats. For this, the baroreflex activity was assessed using two approaches: i) the pharmacological approach via intravenous infusion of vasoactive agents, and ii) the sequence analysis technique that evaluates reflex responses during spontaneous arterial pressure variations. The sequence analysis technique indicated that LH treatment with the selective CRF1 receptor antagonist CP376395 decreased the baroreflex effectiveness index, whereas the selective CRF2 receptor antagonist antisauvagine-30 increased the reflex shortening of pulse interval during spontaneous arterial pressure decreases. However, the pharmacological approach did not indicate effect of the bilateral microinjection of either CP376395 or antisauvagine-30 into the LH in the tachycardia evoked by blood pressure decrease or the reflex bradycardia caused by blood pressure increase. Overall, these findings indicate that CRF neurotransmission within the LH controls baroreflex function during a narrow range of physiological arterial pressure variations. Besides, results provide evidence that CRF1 and CRF2 receptors in the LH oppositely modulate the spontaneous baroreflex activity through different mechanisms.